Pests that Occasionally Invade Structures - P.G. Koehler; J.L. Castner (EDIS)
This document provides an overview of various pests that occasionally invade structures, including silverfish, ground beetles, scorpions, thrips, crickets, scarab beetles, bark beetles, ambrosia beetles, long-horned wood boring beetles, and plaster bagworms. It describes their physical characteristics, habitats, and behaviors, emphasizing the conditions that lead to infestations. The publication highlights the importance of understanding these pests for effective management and control. Original publication date January 1994.